Delineation of estuarine ecological corridors using the MaxEnt model to protect marine fishery biodiversity - He, Yanlong; Zhao, Lixia; Liu, Shouhai; Zhao, Xin; Wang, Yutan; Jiang, Xiaoshan (Frontiers in Marine Science, 2022)
Ecological corridors (ECs) are important management tools to protect biodiversity by linking fragile habitats, especially for highly mobile organisms. ECs in terrestrial landscapes work as passages on land or in water. However, the significance of ECs to migratory species in estuaries has not been well elucidated. Based on annual fishery investigation in the Yangtze estuary and their dominance index rank, three of the top five species, including Larimochthys polyactis, Coilia mystus, and Gobiidae, exhibited absolute dominance in spring during the past 5 years. The temporal and spatial density variance of C. mystus supported its short-distance migration pattern. Redundancy analysis and the MaxEnt model predicted optimum habitats for C. mystus. C. mystus larvae survival was significantly related to salinity, total nitrogen, pH, reactive silicate, dissolved oxygen, surface water temperature, and chlorophyll-a in May and to salinity, surface water temperature, permanganate index, suspended particles, total nitrogen, and total phosphorus in August. The MaxEnt model predicted a broader longitudinal distribution range from offshore to the upstream freshwater area but narrower latitudinal distribution in the southern branch in May than in August. Finally, we delineated migratory corridors connecting optimum habitats for C. mystus using the least-cost route method. Optimum habitats close to the coastlines in the south branch might play a significant role in maintaining population or community connectivity in the Yangtze estuary. Our findings provide a perspective and method to quantify and facilitate the harmonious development of socioeconomy and fishery biodiversity conservation.